2012
DOI: 10.1098/rsif.2011.0910
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-layered bird beaks: a finite-element approach towards the role of keratin in stress dissipation

Abstract: Bird beaks are layered structures, which contain a bony core and an outer keratin layer. The elastic moduli of this bone and keratin were obtained in a previous study. However, the mechanical role and interaction of both materials in stress dissipation during seed crushing remain unknown. In this paper, a multi-layered finite-element (FE) model of the Java finch's upper beak (Padda oryzivora) is established. Validation measurements are conducted using in vivo bite forces and by comparing the displacements with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…An earlier study on Padda oryzivora [23] showed that changing the bone modulus value also had a linear effect, albeit small, on safety factor values (SFs changed from 2.5 to 3.0 if bone modulus changed from 6.7 to 7.9 GPa). Also, variation in the keratin modulus within its measured interval (Eker = 1.3 till 2.1 GPa) had a little effect on SF.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study on Padda oryzivora [23] showed that changing the bone modulus value also had a linear effect, albeit small, on safety factor values (SFs changed from 2.5 to 3.0 if bone modulus changed from 6.7 to 7.9 GPa). Also, variation in the keratin modulus within its measured interval (Eker = 1.3 till 2.1 GPa) had a little effect on SF.…”
Section: Discussionmentioning
confidence: 99%
“…Validation experiments on the beaks of extant finches have shown that these assumptions yield high correlations between ex vivo experimental displacements and displacements from skull and beak FE models (R 2 = 0.97 for loading at the anterior rostrum, R 2 = 0.89 loading elsewhere along the beak). Thereby our methodology for FE model construction can be considered valid and biologically realistic (10).…”
Section: Methodsmentioning
confidence: 99%
“…Apparently freed from functional constraints associated with a carnivorous diet, this permitted diversification of skull and beak shapes, particularly among extant and extinct birds (9). Biomechanical studies on extant birds have indicated a functional benefit of rhamphothecae and beaks other than weight reduction (10,11). However, the functional role of edentulism and (keratinous) beaks in the evolution of herbivory from a macropredaceous heritage is still unclear.…”
mentioning
confidence: 99%
“…This allows the mechanical function of complex structures, such as the skull and the masticatory apparatus, to be studied in a non‐invasive way. The FE method has been used to investigate cranial morphology and feeding biomechanics in many taxa, including mammals, reptilian sauropsids, birds, and dinosaurs (e.g., Rayfield, ; Dumont et al, ; McHenry et al, ; Jasinoski et al, ; Tseng and Wang, ; Attard et al, ; Dumont et al, ; Cox et al, ; Oldfield et al, ; Soons et al, ; Young et al, ; Piras et al, ; Figueirido et al, ; Gill et al, ;).…”
Section: Introductionmentioning
confidence: 99%